A protocol for the development of reporting criteria for surgical case reports: The SCARE statement. (March 2016) - Agha, Riaz A.; Fowler, Alexander J.; Saetta, Alexandra; Barai, Ishani; Rajmohan, Shivanchan; Orgill, Dennis P.; ,
Abstract: Introduction: Case reports have specific relevance within the surgical literature. The Case Report Guidelines (CARE) were developed in 2013 to provide a framework to support accuracy in the publication of case reports. As such, they have been adopted by multiple journals. However, they are not tailored to surgery. The objective of this research is to conduct a Delphi consensus exercise amongst experienced case report reviewers and editors to develop the Surgical CAse REport (SCARE) Guidelines. Methods and analysis: The CARE statement will be used as the basis for this Delphi consensus exercise. The Delphi questionnaire will be administered via SurveyMonkey and conducted using standard Delphi Methodology. Surgeons and others with significant experience in reviewing case reports will be invited to participate. There is no pre-determined number of Delphi rounds, although the expectation is that at least three will be needed. Initially, interested parties will be invited to contribute further items for consideration. Then, in each subsequent round, the participants will rate the importance of reporting each outcome on a nine-point Likert scale as proposed by the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) working group. This process will also be used to agree standard definitions for the outcomes. Dissemination: This work will be disseminated through publication and will be presented at national and international meetings. The findings will be disseminated to interested parties, and journals will be encouraged to endorse the reporting guideline. Highlights: Case Report Guidelines (CARE) are a framework to support the preparation of case reports, but they are not surgery specific. Aim to conduct Delphi consensus exercise to develop the Surgical CAse REport (SCARE) Guidelines. This process will also be used to agree standard definitions for the outcomes. Dissemination to interested parties, and journals will be encouraged to endorse the reporting guideline.